Improved nanopore direct RNA sequencing of cardiac myocyte samples by selective mt-RNA depletion - Naarmann-de Vries, Isabel S.; Eschenbach, Jessica; Dieterich, Christoph (Journal of molecular and cellular cardiology, 2022)
RNA sequencing is a powerful tool to analyze gene expression transcriptome wide. However, RNA sequencing in general and especially the recently developed methods of long read RNA sequencing are still low-throughput and cost-intensive. Here, one important design choice is to concentrate the sequencing capacity on specific parts of the transcriptome. Especially, abundant transcripts as ribosomal RNAs may dominate the available sequencing space, if not removed prior to sequencing. Several methods exist to reduce ribosomal RNA read numbers: either based on enrichment of the relevant fraction (polyA+ RNA) or depletion, respectively degradation of ribosomal RNAs. Furthermore, commercial kits are available to deplete globin transcripts from blood samples. However, so far, no solution exists to deal with other tissue-specific highly abundant transcripts. This is especially of interest in the heart and other muscle derived samples, where reads originating from mitochondrial RNAs make up to 30% of reads in polyA+ selected libraries and around 70% in single cell sequencing experiments. We present a simple method to diminish sequencing of mitochondrial RNAs in Oxford Nanopore direct RNA sequencing libraries by RNase H based clipping of the polyA tail. We show that mt-clipping enables enhanced detection of cytoplasmic mRNAs, among them genes involved in heart development and pathogenesis. Mt-clipping may be applied as well to other sequencing protocols that are based on oligo(dT) priming and can be easily adapted to other tissue-specific high-abundant transcripts.